SOIL FERTILITY STATUS AND SOYBEAN [Glycine max (L) Merr] PERFORMANCE FOLLOWING INTRODUCTION OF INDIGENOUS MYCORRHIZA COMBINED WITH VARIOUS NUTRIENT SOURCES INTO SANDY SOIL - Astiko, Wahyu; Sastrahidayat, Ika Rocdjatun; Djauhari, Syamsuddin; Muhibuddin, Anton (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
The experiment tested four treatments, namely inoculation of soil with mycorrhiza, inoculation of soil with mycorrhiza and cattle manure, inoculation of soil with mycorrhiza and rock phosphate, and inoculation of soil with mycorrhiza and inorganic fertilizers. Soil without any inoculation was provided as control. The treatments were arranged in a Completely Randomized Design with four replications. Soil fertility status was based on the concentrations of N, P, K, and organic-C as well as soil pH. Plant performance was determined based on its ability to uptake nutrients (N, P, K, and Ca), its growth and yield. Then, the activity of mycorrhiza was measured based on total population and percentage of root infection. Overall, results of the present study showed that, compared with other treatments, inoculation of mycorrhiza into soil and amended with cattle manure significantly performed higher concentrations of N, P, K, and organic-C. This soil condition caused soybean to absorb significantly higher nutrients, grew well with higher yield compared with plant performance in other treatments. Therefore, results of this study implies that the application of mycorrhiza into soil amended with organic matter is promising to sustain soil productivity under soybean cropping system. Â Keywords: Arbuscular Mycorrhiza, soil fertility, soybean yield, dryland